2023
DOI: 10.1021/acs.langmuir.2c03049
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanisms of Hexagonal Boron Nitride Nanosheets in Solvothermal Exfoliation

Abstract: Solvothermal techniques are widely used to exfoliate many two-dimensional materials, but the formation mechanisms of these nanomaterials have not been clearly revealed. Herein, we discovered the dissociation of hexagonal boron nitride (h-BN) in solvothermal exfoliation evidenced by the formation of B(OH) 3 , NH 4 B 5 O 8 •4H 2 O, and (NH 4 ) 2 B 10 O 16 •8H 2 O. In the selected solvents, the lateral sizes of the formed boron nitride nanosheets (BNNSs) are increased in the order of N-methyl-2-pyrrolidone (NMP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Reproduced with permission from Songfeng et al. 45 Copyright © 2023, American Chemical Society. (C) Schematic illustration of the CVD growth route.…”
Section: Synthetic Methods Of 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission from Songfeng et al. 45 Copyright © 2023, American Chemical Society. (C) Schematic illustration of the CVD growth route.…”
Section: Synthetic Methods Of 2d Materialsmentioning
confidence: 99%
“…Songfeng et al. 45 revealed the formation mechanisms of these nanomaterials by solvothermal techniques. As shown in Figure 1 B, it was revealed that hexagonal boron nitride (h-BN) dissociates in solvothermal exfoliation.…”
Section: Synthetic Methods Of 2d Materialsmentioning
confidence: 99%
“…154 Finally, in 2023, E and coworkers studied the mechanism of solvothermal exfoliation. 155 They first pre-treated their hBN by ball In 2018, Rizvi and coworkers described a different approach using expansion of high-pressure gas to exfoliate several 2D nanomaterials, which was named compressible flow exfoliation (CFE). This strategy presented several advantages including being a faster, continuous process and producing fewer defects on the materials.…”
Section: Thermal Expansionmentioning
confidence: 99%
“…154 Finally, in 2023, E and coworkers studied the mechanism of solvothermal exfoliation. 155 They first pre-treated their hBN by ball milling, then sonicated the powder in either NMP, DMF, acetonitrile, or IPA. They found that the addition of LiCl and cetyltrimethyl ammonium bromide (CTAB) during the sonication process improved the dissociation of hBN, where the Li + ions and CTAB were suggested to intercalate the hBN layers through cation–π interactions.…”
Section: Thermal Expansionmentioning
confidence: 99%
See 1 more Smart Citation